GENERATION Z WOMEN'S MEANING OF STANDARDSBEAUTY ON THE BEAUTY LECTURER'S TIK TOK ACCOUNT - Irene Silviani; Emilia Debora (LPPM YPITI, 2025)
This study aims to understand how female beauty standards are constructed through the TikTok account @dosenkecantikan, and how Generation Z interprets and responds to these standards. TikTok has become a dynamic platform where beauty ideals are formed, disseminated, and internalized.Using a qualitative approach, this research is based on in-depth interviews with members of Generation Z who actively consume beauty content on TikTok. The analysis focuses on patterns of internalization, self-comparison, and critical reflection on the promoted beauty standards. The results show that @dosenkecantik consistently displays idealistic beauty standards, which influence how viewers perceive themselves. Repeated exposure encourages internalization, although some viewers demonstrate awareness. This reflects the tension between the urge to conform to popular beauty standards and the desire to maintain personal uniqueness. This research confirms the role of social media in shaping beauty perceptions among Generation Z, as well as its contribution to the construction of social reality in the digital age